Targeted inhibitors and antibody immunotherapies: Novel therapies for paediatric leukaemia and lymphoma. (March 2022) - Brivio, Erica; Baruchel, André; Beishuizen, Auke; Bourquin, Jean-Pierre; Brown, Patrick A.; Cooper, Todd; Gore, Lia; Kolb, E. Anders; Locatelli, Franco; Maude, Shannon L.; Mussai, Francis J.; Vormoor-Bürger, Britta; et al.
Abstract: Despite improved outcomes achieved in the last decades for children with newly diagnosed leukaemia and lymphoma, treatment of patients with refractory/relapsed disease remains a challenge. The cure rate is still unsatisfactory and often achieved at the cost of significant morbidity. Exploring treatment with novel agents should offer less toxic therapeutic options, without compromising efficacy. Bispecific and antibody–drug conjugates targeting CD19 and CD22 (blinatumomab and inotuzumab ozogamicin) play an important role in the treatment of relapsed and refractory B-cell precursor acute lymphoblastic leukaemia (BCP-ALL); antibodies targeting CD123 and CD38 are also under investigation for acute myeloid leukaemia (AML) and T-ALL, respectively. Targeted therapy with small molecules is of primary importance for specific genetic subtypes, such as BCR-ABL-positive ALL, FLT3- ITD AML and anaplastic lymphoma kinase (ALK)-positive anaplastic large cell lymphoma. KMT2A -directed targeted therapy with menin inhibitors holds promise to be of relevance in KMT2A -rearranged leukaemias, known to have dismal prognosis. Target inhibition in cellular pathways such as BCL-2, RAS, MEK, Bruton's tyrosine kinase, JAK-STAT or CDK4/CDK6 inhibition may be suitable for different diseases with common mutated pathways. Nevertheless, development and approval of new agents for paediatric cancers lags behind adult therapeutic options. New regulations were implemented to accelerate drug development for children. Considering the number of oncology medicinal products available for adults and the rarity of paediatric cancers, prioritisation based on scientific evidence and medical need, as well as international collaboration, is critical. Herein, we review the current status of drug development for children with leukaemia and lymphoma, excluding cellular therapy despite its well-known significance. Highlights: Development and approval of new agents for paediatric cancers lags behind adult options. We provide an overview of available novel agents for paediatric leukaemia and lymphoma. Recent and upcoming early phase trials in this field are presented. Challenges and foreseen changes in the landscape are discussed.